Excited-Nucleon Spectroscopy with 2+1 Flavour Fermions - RYAN, SINEAD MARIE (My University, 2009)
We present progressmade by the Hadron SpectrumCollaboration (HSC) in determining the tower of excited nucleon states using 2+1-flavor anisotropic clover lattices. The HSC has been investigating interpolating operators projected into irreducible representations of the cubic group in order to better calculate two-point correlators for nucleon spectroscopy; results are published for quenched and 2-flavor anisotropic Wilson lattices. In this work, we present the latest results using a new technique, distillation, which allows us to reach higher statistics than before. Future directions will be outlined at the end.
PUBLISHED
Keywords: Mathematics; Particle Physics